Atherosclerosis Technologies of Personalized Medicine - Ragino, Yuliya I. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The first national conference with international participation, "Fundamental aspects of atherosclerosis: scientific research for improving the technologies of personalized medicine", was held in Novosibirsk on 15 October, 2021. The purpose of this conference was to disseminate the latest basic and clinical findings in the fields of etiology, clinical characteristics, and modern diagnostics and treatments of atherosclerosis among various relevant specialists. The conference was intended for practicing cardiologists, primary care physicians, medical geneticists, and physician-scientists. The conference included plenary sessions, specialty sessions, satellite symposia, an open competition for young scientists.